2014
DOI: 10.1002/chem.201402648
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Guanidinate‐Stabilised Diboranes: Transition‐Metal‐Catalysed Dehydrocoupling and Hydride Abstraction

Abstract: Herein, we analyse the catalytic boron-boron dehydrocoupling reaction that leads from the base-stabilised diborane(6) [H2 B(hpp)]2 (hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) to the base-stabilised diborane(4) [H2 B(hpp)]2 . A number of potential transition-metal precatalysts was studied, including transition-metal complexes of the product diborane(4). The synthesis and structural characterisation of two further examples of such complexes is presented. The best results for the dehydrocoupling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
11

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 102 publications
0
40
0
11
Order By: Relevance
“…The dehydrogenative cyclization of diaminemonoboranes has been reported to form cyclic diaminoboranes using a Ru(PCy 3 ) 2 (H 2 ) 2 (H) 2 catalyst; [23, 24] the metal-catalyzed dehydrocoupling of base-stabilised diborane(6) [H 2 B(hpp)] 2 to give [HB(hpp)] 2 (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) has been reported, alongside subsequent coordination chemistry; [25, 26] and there is an early report of sigma complexes formed from cyclic diboranes. [27] Shore and co-workers have developed the coordination chemistry and reactivity of related cyclic anionic organohydroborates of the early transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…The dehydrogenative cyclization of diaminemonoboranes has been reported to form cyclic diaminoboranes using a Ru(PCy 3 ) 2 (H 2 ) 2 (H) 2 catalyst; [23, 24] the metal-catalyzed dehydrocoupling of base-stabilised diborane(6) [H 2 B(hpp)] 2 to give [HB(hpp)] 2 (hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) has been reported, alongside subsequent coordination chemistry; [25, 26] and there is an early report of sigma complexes formed from cyclic diboranes. [27] Shore and co-workers have developed the coordination chemistry and reactivity of related cyclic anionic organohydroborates of the early transition metals.…”
Section: Introductionmentioning
confidence: 99%
“…This compound is also considered for hydrogen storage applications as it delivers up to eight equivalents of H 2 upon hydrolysis and five equivalents of H 2 upon thermolysis. Thef irst example was prepared by reaction of the especially nucleophilic sp 3 -sp 3hybridized dihydrodiborane [HB(hpp)] 2 [48][49][50] with the strongly electrophilic boranes N-borabicyclo[3.3.1]nonan-9yl (9-BBN) trifluoromethanesulfonateo rb is(trifluoromethanesulfonyl)imide (Scheme 10 a). [47] Thef ormal addition of three hydrides and two neutral two-electron donor ligands Lto(B 3 H 3 ) 4+ leads to amonocation (B 3 H 6 L 2 ) + that could alternatively be described as ad ouble base-stabilized (B 3 H 6 ) + analogue.D erivatives of this compound are indeed known.…”
Section: Methodsmentioning
confidence: 99%
“…[HB(μ-hpp)] 2 was synthesized as reported previously. [23] B(C 6 F 5 ) 3 was delivered from Strem Chemicals, purified by sublimation, and stored in a glove box (MBraun LABmaster dp, MB-20-G) under argon. IR spectra were recorded with a BIORAD Excalibur FTS 3000 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…[18] A starting reagent in our research in this area is the diborane [HB(hpp)] 2 (2; see Scheme 2, a; hpp = 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate), which can be synthesized in high yield in a one-pot reaction from commercially available hppH and H 3 BǟNMe 3 (see Scheme 2,a). [20][21][22][23] We recently showed that hydride abstraction from [HB(hpp)] 2 (2) with B(C 6 F 5 ) 3 [24] results in the formation of the dication [H 2 B 4 (hpp) 4 ] 2+ (3) with a four-electron, fourcenter bond between the four boron atoms (see Scheme 2,b work, it was not possible to capture the postulated intermediate cation 4, which is isolobal to the ethyl cation. As opposed to the "nonclassical" structure with one bridging hydrogen atom of the ethyl cation, [25,26] quantum chemical calculations predict that 4 has a terminal B-H bond.…”
Section: Introductionmentioning
confidence: 98%